Anger and Physical and Psychological Health. A Narrative Review - Vicente Palop-Larrea (Revista de Estudios Sociales, 2024)
With the advent of modern Medicine, the connections between emotions and medical conditions have primarily been described through observational studies, where conclusions are drawn from correlations of observations rather than experimental research. Psychoanalytical theory has often been used to explain many common illnesses. This approach remains prevalent today. Interestingly, despite the wealth of information now available on the influence of emotions on health, the current divide between neurology and psychiatry, as well as the separation between mental health services and primary care, combined with the time constraints and physicians’ workload, have led to a fragmented approach to many disorders. In these cases, psychological and emotional factors play an important role but are often inadequately addressed. The objective of this paper is to analyse the existing evidence on the relationship between anger and health through a narrative review. The evidence and data presented point to the need for analytical studies based on scientific methodology to explore the relationship between anger and health, and particularly to adopt an integral health approach taking into account social determinants and the role of empathy among the healthcare professionals and clinical and social care. The prevention and treatment of problems related to the high prevalence and intensity of anger are particularly relevant, given the potential negative impact this emotion can have on patients’ physical and mental health, as well as their social adjustment and relationships.